Controvérsias científicas e tecnológicas no jornal “A província de São Paulo” : 1875-1889 - Berbel, Danilo Brancalhão (2017)
Brazil changed after the Potuguese Royal Family arrives in 1808. One of it was the founda-tion of the Royal Press and the law that allowed to print books and newspapers in Brazilian soil. There are a lot of social, educational and political changes since then. Scientific re-searches are developed and technological systems are deployed, brought from Europe. In 1875, “A Provincia de São Paulo” was created associated to republican and abolitionsit groups, showing the news in São Paulo, Brazil and in the world. In that time, science and technology were becoming common at the urban life and generated public discussions. The newspaper is a plivilage sphere to circulate ideas about that. The objective of this thesis is to analyze the publications about science and technology in that journal about two themes: the Teory of Evolution and the gauges standardization in the construction of the railroads in Bra-zil. The analysis of the controversies is the specific objective. The analysis methodology is composed by two steps: the first one works with boards, facilitating the categorization and description, that shows all publicated information in the scientific and technological sections of the newspaper: “Secção Scientifica” and “Secção Industrial”. The second methodological step is based on the Social Studies of Science and Technology, specifically in two theoretical currents: the Empirical Programme of Relativism (EPOR) and the Social Construction of Technology (SCOT). The categories of analizys come from this theorical and methodological approach, that allow to identify authors and contextualize them to the social and historical analyzed period, to observate motivations, approaches, informations, editorial lines, biases and arguments about the clash involving the scientific theories and technological develop-ment. The time cut comprises from the inauguration of “A Província de São Paulo”, in Janu-ary 4th 1875, to the year of the Republic Proclamation, until December 1889. The first analy-sis refers to the discussion of railroad technology and the controversy over the standardization of gauges. There are two sides: the first one defends the narrow gauge (there are less technical information and more authorial retorical) and the second one defends the large gauge (there are more scientific and technological references). These discussions were between two engi-neers and shareholders of the “Companhia Paulista” with economic interests about the rail-road development. The temporary closure was in favor of the large gauge. The second analy-sis is about the discussion of the Theory of Evolution between 1875 and 1886, involving mostly the defense of the Darwinists ideas. In two moments, authors of different thoughts discussed in the pages of the newspaper. They were, mostly, men of science and defended these interests groups. As a result, they created favorable and receptive agendas to Darwin‟s theories. In both cases, it was possible to evidence the motivations and the artifices involved in the contest, which includes epistemic and non-epistemic arguments, confirming the social construction of technological and scientific processes.